Concept of Dance as described in Agni Purana - Renuka N. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
Agni Purana is one of the eighteen Puranas. It is a voluminous work having as many as about 15, 000 verses, spread over 385 Chapters. The Agni Purana is a sort of encyclopedia that deals with wide-ranging subjects. Chapters 340 and 341, give some information about Dance, particularly relating to Anga-karma Abhinaya (actions, gestures, and movements). This puranic literature contains several references to dance and music which cannot be ignored. The main purpose of the study is to examine the aesthetic value of the Natyashastra as well as its religious implications by examining all chapters pertaining to dance from the Agni Purana. This study is appropriate for the analytical research methodology. It attempts to critically analyse the information about Nrtyadi-ranga-karma, which is a brief study of bodily actions in Dance. Puranas have been influencing the value and purpose of life throughout the centuries and are valuable, as they supply the materials for the study of diverse subjects such as geography, cultural history, politics, education system, iconography, medicine, grammar, poetry, Alamkara, Chhandas, Rasa, Riti, Yoga and all fine arts including dance and music and this research paper is limited to only dance.